Molecular Targets and Emerging Therapies for Advanced Gallbladder Cancer - Matteo Canale (MDPI AG, 2021)
Biliary tract cancers (BTCs), for their low incidence, have been often considered together. Gallbladder cancer (GBC) is the most common biliary tract malignancy, characterized by late diagnosis and poor prognosis, and although it is considered a rare tumor in western countries, other areas of the world show considerable incidence rates. In 2010, results from the large phase III ABC-02 clinical trial on GBC identified the gemcitabine and cisplatin combination as the most effective first-line regimen for both GBC and other BTCs. Since then, various systemic therapies have proven active in BTCs in both first- and second-line settings. Molecular profiling has highlighted important genetic differences between GBC and other BTCs, opening new ways for targeted therapy in advanced disease where standard chemotherapies show marginal benefit. Genome-wide data analysis have shown that GBC molecular landscape offer possible strategies for precision medicine approaches, and a better molecular understanding of the GBC is needed to better stratify patients for treatment. In this review, we discuss the molecular targetable agents for GBC, including the results that emerged by clinical trials exploring new treatment strategies.